SDG 12 Responsible Consumption and Production: Evidence From Manufacturing Companies in Taytay, Rizal - Toledo, Jr., Alfredo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the implementation of Sustainable Development Goal 12 (SDG 12) on Responsible Consumption and Production among food and beverage manufacturing companies in Taytay, Rizal, Philippines. Specifically, it described the respondents’ personal and business profiles, determined the extent of SDG 12 implementation across the eleven (11) target areas, examined significant differences in the respondents’ assessments according to selected profile variables, and developed an SDG 12 Compliance Model to strengthen sustainability practices. A quantitative descriptive research design was employed involving 210 managers, production staff, and factory workers from ten (10) registered manufacturing companies selected through simple random sampling using Slovin’s formula. Data were gathered using a researcher-developed questionnaire that underwent expert validation and reliability testing. Statistical treatments included frequency, percentage, weighted mean, independent samples t-test, and one-way analysis of variance (ANOVA).The findings revealed that manufacturing companies generally often practiced SDG 12 principles (Grand Mean = 3.65), with Sustainable Tourism (4.29) and Awareness of Sustainable Development (4.23) receiving the highest ratings. Conversely, the 10-Year Framework Programme (2.48) and Scientific and Technological Capacity (2.77) were the least practiced indicators. No significant overall difference was found between managers’ and staff members’ assessments (p = .656), although significant differences were observed in Reduce Waste Generation (p = .040) and Phasing Out Harmful Subsidies (p = .009). Furthermore, job position, average monthly income, sources of capital, years of engaging in sustainable practices, and number of employees significantly influenced respondents’ assessments. Based on these findings, an SDG 12 Compliance Model was developed to guide manufacturing companies in enhancing sustainability planning, environmental stewardship, and responsible production practices. The study recommends strengthening technological innovation, sustainability policies, and stakeholder collaboration to improve SDG 12 implementation in the manufacturing sector.